TEACHERS’ PERCEPTIONS TOWARDS “WHEN ENGLISH RINGS A BELL” TEXTBOOK AT SOME JUNIOR HIGH SCHOOLS IN ACEH TAMIANG - Veni Nella Syahputri; Zahratul Idami; Murni (Getsempena English Education Journal, 2019)
The relationship between teachers and textbooks is inseparable. But not all textbooks published are suitable with the learners` need and have good qualities. Thus, textbook analysis is needed to evaluate and improve a textbook which is used. Teacher‟s perception plays a fundamental role in the effective implementation of process teaching learning. This study was intended to describe teachers‟ perceptions towards “When English Rings A Bell” textbook at some Junior High Schools in Aceh Tamiang. This research used descriptive qualitative research. The research conducted in four junior high schools at Aceh Tamiang. They were SMP Negeri 1 Karang Baru, SMP Negeri 2 Karang Baru, MTs Swasta Al- Iklas Tanah Terban and SMP Negeri 1 Manyak Payed. In this research there were eight English teachers selected by the researcher as source of the data. The total populations in this research were 10 schools, but the researcher selected 8 English teachers as sample by using purposive sampling technique. In collecting the data, the researcher used documentation, interview and questionnaire. There were 20 interview questions that asking to the teacher and 20 items of the questionnaire. After analyzed the data, the result showed that generally all English teachers had the positive perspective toward “When English Rings A Bell” textbook. Almost all the criterion of good textbooks was included in this book. Although, this book did not support media such as audio recorded on cassette or video. Furthermore, all the teachers believed that textbook selection was important to conduct to make sure that the textbook they choose was suitable for their students.